367. Clinical Characteristics and Outcomes in Patients with Pneumonia secondary to Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). (31st December 2020) - Nichols, Courtney; Sobhanie, Mahdee; Colburn, Nora; Lustberg, Mark; El Boghdadly, Zeinab; Liscynesky, Christina; Hebert, Courtney; Day, Shandra R
Abstract: Background: Since discovery in December 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which causes the disease of COVID-19 has become a global pandemic. Little is known about which risk factors lead to more severe disease or increased mortality in patients diagnosed with SARS-CoV-2. We aimed in this study to compare clinical characteristics associated with disease severity and increased mortality in hospitalized patients with COVID-19. Methods: This was a single-center, retrospective study at The Ohio State University Wexner Medical Center to compare clinical characteristics associated with increased mortality in hospitalized patients with confirmed SARS-CoV-2. Adults patients positive for SARS-CoV-2 between March 1, 2020 and April 20, 2020 were included in the study. Prisoners and pregnant women were excluded. Baseline demographics, clinical characteristics, and outcomes were collected, and then compared to determine association with mortality. Statistical analysis used univariate and multivariate logistic regression analysis to evaluate the relationship between patient characteristics and mortality. Results: The cohort included 92 patients. Median age was 58 years (ranging from 25–93) and 47/92 were men (51%). 12 patients were admitted directly to the intensive care unit (ICU), with 22 additional patients transferred to the ICU. 23 patients required mechanical ventilation. Clinical characteristics significantly associated with mortality in univariate analysis included underlying coronary artery disease (CAD) (OR=7.8, p = 0.002), chronic obstructive pulmonary disease (OR=5.21, p=0.02), living in an extended care facility (ECF) (OR=4.2, p=0.025), and immunocompromised status (OR=4.2, p=0.025). Multivariate analysis showed a statistically significant association in patients with underlying CAD (OR=13.1, p=0.001) and those admitted from an ECF (OR=12.1, p=0.005), when adjusted for other variables in the model. Characteristics Associated with Mortality in Patients with COVID-19 in Univariate Analysis Conclusion: Our study found that CAD and admission from an ECF were associated with SARS-CoV-2 mortality, when adjusted for age and other comorbidities. Further studies are necessary to identify potential preventative strategies to mitigate mortality in this vulnerable population. Disclosures: All Authors : No reported disclosures